The Correlation between Parental Education and Student Outcomes in Nepal: Sustainable Development in Education from the Student Perspective - Adhikari, Sudarshan (Academia Journal of Humanities & Social Sciences, 2026)
Parental education is a key factor influencing students’ academic performance, motivation, and engagement in the sustainable educational development. This study aims to explore the correlation between parental education and student outcomes using a mixed-methods approach to provide a comprehensive perspective from students themselves. Data were collected from 102 students in the selected secondary level schools in Pokhara Metropolitan City, comprising 50 male and 52 female respondents. The stratified random sampling was employed for the survey, while the semi-structured interviews were conducted with the selected students and parents to enrich the quantitative finding. Data analysis was conducted manually using the descriptive statistics and correlation techniques to maintain clarity and transparency. The results of the study indicated a moderate positive relationship between parental education and students’ academic outcomes. Students with more educated parents reported the higher academic performance, stronger motivation, and better access to the learning resources. The parental involvement and supportive home environments were identified as important mediating factors, demonstrating that parental education affects the academic achievement directly and indirectly. Despite lower parental education, some students achieved the satisfactory outcomes, highlighting the role of personal motivation and supportive school environments. Parental education significantly contributes to students’ academic success and the promotion of sustainable educational development in Nepal. The policies aimed at enhancing the parental awareness, fostering the school–family collaboration, and providing the targeted support to students from less educated households are essential to reduce the educational inequalities and foster the long-term human development.